Islamic Religious Education as a Spiritual Coping System: Enhancing Adolescents’ Mental and Emotional Well-Being in a Vocational School Context - Aziz Musthopa; Hildan Bayanillah; Hakim Firmansyah; Achmad Zuhri; Zahrotus Saidah; Siti Maryam Munjiat (J-PAI: Jurnal Pendidikan Agama Islam, 2026)
Although research on spirituality-based education has expanded, limited attention has been given to how Islamic Religious Education (IRE) functions as an institutionalized psychosocial support system within school culture, particularly at the vocational high school level. This study addresses this gap by examining the integration of IRE into school routines and its perceived contribution to adolescents' mental and spiritual well-being. A qualitative phenomenological design was employed, with data collected over one month at SMK Farmasi Muhammadiyah Cirebon through participatory observation, semi-structured interviews, and documentation involving two IRE teachers, two students, and one principal selected through purposive sampling. Data were analyzed using an interactive thematic analysis model, with trustworthiness ensured through triangulation and member checking. Findings indicate that institutionalized IRE practices, including daily Qur'anic recitation, congregational Dhuha and Zuhr prayers, Rohis mentoring, dhikr-reflection sessions, and spiritual counseling, are perceived to enhance emotional regulation, reduce psychological distress, and strengthen spiritual resilience. IRE teachers function not only as instructors but also as relational mentors who create psychologically safe spaces, conceptualized as relational religious pedagogy. The internalization of Islamic values, particularly birrul walidain and social morality, is associated with positive behavioral changes across school and family contexts, demonstrating that structured IRE integration operates as a coherent ecosystem of school-based Islamic coping with broader psychosocial implications and supports the institutionalization of IRE within school mental health systems.